Performance Evaluation of Various Machine Learning Techniques for Human Activity Recognition using Smartphone - Anju, SS; Kavitha, KV (International Journal of Computer Sciences and Engineering, 2019)
The process of Human Activity recognition nowadays had found a wide variety of applications in healthcare and security surveillance. The commonly used smartphones are now available with inbuilt accelerometer and gyroscope sensors. The data collected using these sensors are used for recognizing the activity performed by the person who carries the smartphone. The sensor data collected from these sensors are fed to activity classifiers to train them. In this paper, the performance of various machine learning techniques are trained and evaluated for finding the better classification technique. In particular, examines the use of Decision tree, Naive bayes, K-nearest neighbour, Support Vector Machine and Random forest. The evaluation metrics used are accuracy, sensitivity, specificity and precision. During evaluation the results showed that the SVM showed better accuracy with the smartphone data.